Incidence of dengue fever, climate and vector density in Denpasar - Irma Rubianti; Dewa Nyoman Wirawan; Anak Agung Sagung Sawitri2 (Public Health and Preventive Medicine Archive, 2018)
Background and purpose: Until 2009, Denpasar consistently had the highest rates of dengue fever in Bali. However, from 2010 onwards, dengue rates in Denpasar have declined and in 2017 ranked 7th for incidences of dengue fever in Bali. This study aims to determine the trend and the difference of dengue fever incidence rates, vector density and climate for the period 2007-2017. Methods: This study employed a secondary analysis of dengue fever incidence rates, climate data and vector density from 2007 to 2017. Data on dengue fever incidence, vector density and the number of field workers (known as juru pemantau jentik or jumantik) were obtained from the Denpasar City Health Office. Climate data for 2007-2017 were obtained from the Bali Province Meteorological, Climatological and Geophysical Agency. The data were analyzed by comparing the dengue fever incidence rates, climate data, and vector-density data of the period 2007-2012 and 2013-2017. Results: Incidences of dengue fever in Denpasar have declined since 2013. Climate-related variables found to differ significantly were air temperature, humidity, wind speed and sunlight duration. Air temperature (p=0.03) and wind speed (p<0.01) were significantly higher in 2013-2017 compared to the period of 2007-2012. Humidity and sunlight duration were significantly lower (p<0.01) in 2013-2107 compared to the period of 2007-2012. Rainfall was lower in 2013-2017 compared to the period of 2007-2012, however, the difference was not significant (p=0.57). The proportion of larva-free households was significantly higher (p<0.01) in 2013-2017 (96.9%) compared to the period of 2009-2012 (95.3%). The data of house index (HI), container index (CI) and Breteau index (BI) cannot be compared between these two periods because they are only available for 2013-2017. Conclusion: There has been a decrease in the incidence of dengue fever in Denpasar from 2013-2017 compared to 2007-2012. This is likely to be related to the performance of jumantik in the implementation of vector control programme (VCP) in Denpasar.